A novel biologically-based approach to evaluating soil phosphorus availability across complex landscapes. (September 2015) - DeLuca, Thomas H.; Glanville, Helen C.; Harris, Matthew; Emmett, Bridget A.; Pingree, Melissa R.A.; de Sosa, Laura L.; Cerdá-Moreno, Cristina; Jones, Davey L.
Abstract: Plants employ a range of strategies to increase phosphorus (P) availability in soil. Current soil P extraction methods (e.g. Olsen P), however, often fail to capture the potential importance of rhizosphere processes in supplying P to the plant. This has led to criticism of these standard approaches, especially in non-agricultural soils of low P status and when comparing soil types across diverse landscapes. Similarly, more complex soil P extraction protocols (e.g. Hedley sequential fractionation) lack functional significance from a plant ecology perspective. In response to this, we present a novel procedure using a suite of established extraction protocols to explore the concept of a protocol that characterizes P pools available via plant and microbial P acquisition mechanisms. The biologically based P (BBP) extraction was conducted by using four extractions in parallel: (1) 10 mM CaCl2 (soluble P); (2) 10 mM citric acid (chelate extractable P); (3) phytase and phosphatase solution (enzyme extractable organic P); (4) 1 M HCl (mineral occluded P). To test the protocol, we conducted the analyses on a total of 204 soil samples collected as part of a UK national ecosystem survey (Countryside Survey) in 1998 and repeated again in 2007. In the survey, Olsen P showed a net decline in national soil P levels during this 10 year period. In agreement with these results, soluble P, citrate extractable P and mineral occluded P were all found to decrease over the 10 year study period. In contrast, enzyme extractable organic P increased over the same period likely due to the accumulation of organic P in the mineral soil. The method illustrates a noted shift in P pools over the 10 year period, but no net loss of P from the system. This new method is simple and inexpensive and therefore has the potential to greatly improve our ability to characterise and understand changes in soil P status across complex landscapes. Highlights: Existing soil phosphorus (P) methods do not reflect plant P acquisition strategies. We combine four P extraction procedures as a biologically based P protocol. Soluble and acid extractable P correlated well with existing P methods. Enzyme extracted P defined bioavailable organic P. The method was effective in assessing P availability across complex landscapes.